On the Theory of NP-Complete Problems - Listrovoy, S.V. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
It is shown that the theory of NP -Ñomplete problems can't be used for the analysis of optimizing tasks.